AN EXAMPLE OF HOUSING STRUCTURE IN ÇANKIRI: DILBER YEŞILDAG HOUSE - Uğur DEMİRBAĞ (Fırat University, 2020)
Traditional houses are the cultural assets that make it important with its local values. The residence consists of a city and the cultural identity of the region. The traces of the past, which vary according to the city, the locality and the region, and the cultural assets, provide the formation of the unique texture of the city. Anatolia, which has hosted many civilizations in the historical process, has the world’s leading ancient and rich cultural heritage. It is among the most important duties of all societies to keep these accumulations alive and transfer them to future generations. The archaeological excavations carried out in Cankırı reveal the existence of an uninterrupted settlement since the Paleolithic period. Çankırı city, which is one of the oldest settlements of Central Anatolia, has its own civil architecture. Cankırı has been an important center for the relations and cultures of civilizations. In addition to the mound, tumulus, rock tombs and settlements of the antique period, above ground settlement and necropolis areas, there are also underground settlements thought to be made for the purpose of worship and religious and civil architectural works enrich the region in a historical and cultural sense. The civilian architecture in the central district of Çankırı consists of the houses opening to the neighborhoods and streets, starting from the skirts of the Çankırı Castle and opening to the plain on the east-west axis, on the streets formed by partially interlocking streets. However, the city of Çankırı has been transformed into a large structure in recent years and the civil structures that have lost their originality in this structure have been destroyed and transformed into a civilian architecture which has been tried to be protected by being registered.